2014
DOI: 10.1007/s10493-014-9846-3
|View full text |Cite
|
Sign up to set email alerts
|

Inter-population variation for Wolbachia induced reproductive incompatibility in the haplodiploid mite Tetranychus urticae

Abstract: Recent studies have revealed diverse patterns of cytoplasmic incompatibility (CI) induced by Wolbachia in the two spotted spider mite (Tetranychus urticae Koch). The mechanism of CI consists of two steps: modification (mod) of sperm of infected males and the rescue (resc) of these chromosomes by Wolbachia in the egg, which results in female embryonic mortality (FM), male development (MD) or no CI. Our study reports that Wolbachia infections were highly prevalent infecting all T. urticae populations from variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…In particular, use of 16S rDNA PCR with bacterial species-specific primers has been widely used for bacterial taxonomic studies in mites (Fig. For example, the protein-coding genes: ftsZ, groEL, wsp and citrate synthase (gltA) were used in Wolbachia studies (Hong et al 2002;Gotoh et al 2005;Yu et al 2011;Lu et al 2012;Ros et al 2012;Suh et al 2014;Glowska et al 2015;Zhang et al 2015); outer membrane protein B gene, 17 kD antigenic gene and gltA were used for Rickettsia spp. Additionally, several publications used specific PCR to amplify other bacterial genes of interest.…”
Section: Methodological Approaches To the Identification Of Bacteria mentioning
confidence: 99%
“…In particular, use of 16S rDNA PCR with bacterial species-specific primers has been widely used for bacterial taxonomic studies in mites (Fig. For example, the protein-coding genes: ftsZ, groEL, wsp and citrate synthase (gltA) were used in Wolbachia studies (Hong et al 2002;Gotoh et al 2005;Yu et al 2011;Lu et al 2012;Ros et al 2012;Suh et al 2014;Glowska et al 2015;Zhang et al 2015); outer membrane protein B gene, 17 kD antigenic gene and gltA were used for Rickettsia spp. Additionally, several publications used specific PCR to amplify other bacterial genes of interest.…”
Section: Methodological Approaches To the Identification Of Bacteria mentioning
confidence: 99%
“…The two-spotted spider mite, Tetranychus urticae Koch, is a cosmopolitan agricultural pest with an extensive host plant range and strong pesticide resistance (Van Leeuwen et al, 2010;Attia et al, 2013). In T. urticae, Wolbachia was detected in all surveyed populations, with the infection rate varying from 2.5 to 80% (Xie et al, 2006), and was reported to induce variable phenotypes of CI, ranging from no CI to complete CI (Vala et al, 2000(Vala et al, , 2002Perrot-Minnot et al, 2002;Xie et al, 2011;Zhao et al, 2013;Suh et al, 2015;Sun et al, 2016). T. urticae is haplodiploid, which means the fertilized eggs have two sets of chromosomes and develop into diploid females, whereas the unfertilized eggs have only one set of chromosomes and develop into males.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Wolbachia being maternally transmitted, it should always benefit from a more female-biased sex ratio. Note that, although Wolbachia may induce cytoplasmic incompatibility in T. urticae (Gotoh et al , 2007, Xie et al , 2011, Suh et al , 2015), the effects observed in this study on spider-mite sex ratio cannot be attributed to this phenotype as it involves a cross between infected males and uninfected females, which was not performed here. On purple, we could expect the prevalence of Wolbachia to be intermediate, as the infection decreases egg hatchability but increases female proportion.…”
Section: Discussionmentioning
confidence: 81%
“…Among them, Wolbachia is the most prevalent (Liu et al , 2006, Gotoh et al , 2007, Ros & Breeuwer, 2009, Zhang et al , 2016, ZĂ©lĂ© et al , 2018) and induces variable fitness effects in spider mites. For instance, it can decrease (Perrot-Minnot et al , 2002, Suh et al , 2015), not affect (Breeuwer, 1997, Vala et al , 2000, Perrot-Minnot et al , 2002, Vala et al , 2002, Gotoh et al , 2007), or increase (Vala et al , 2002, Gotoh et al , 2007, Xie et al , 2011) their fecundity. Given these variable effects, it is as yet unclear whether Wolbachia will facilitate or hamper host-plant colonization by spider mites.…”
Section: Introductionmentioning
confidence: 99%